Real Time Monitoring and the New Information Technologies1. (21st March 2013) - Lucas, Henry; Batchelor, Simon; Berdou, Evangelia
Abstract Debates as to the potential role of new Information and Communication Technologies (ICTs) in monitoring the wellbeing of vulnerable groups is often bedevilled by the failure of two principal actors – social researchers and technical experts – to address the other's concerns or even to use language that is comprehensible to the other side. The aim here is to unpick some of the technical language relevant in this context and provide a brief introductory guide to some aspects of the current, rapidly changing and highly diverse ICT environment.